Estimating the Economic Burden of Rheumatoid Arthritis in Taiwan Using the National Health Insurance Database - Wang, Bruce C. M. (Drugs Real World Outcomes, 2016)
BACKGROUND: Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by inflammation and destruction of the joints. OBJECTIVES: This research aims to estimate the economic burden of RA in Taiwan. METHODS: The National Health Insurance Research Database (NHIRD), a claims-based dataset encompassing 99 % of Taiwan’s population, was applied. We used a micro-costing approach for direct healthcare costs and indirect social costs by estimating the quantities and prices of cost categories. Direct costs included surgeries, hospitalizations, medical devices and materials, laboratory tests, and drugs. The costs and quantities of the direct economic burden were calculated based on 2011 data of NHIRD. We identified RA patients and a control cohort matched 1:4 on demographic and clinical covariates to calculate the incremental cost related to RA. Indirect costs were evaluated by missed work (absenteeism) and worker productivity (presenteeism). For the indirect burden, we estimated the rate of absenteeism and presenteeism from a patient survey. Costs were presented in US dollars (US$1 = 30 TWD). RESULTS: A total of 41,269 RA patients were included in the database with incremental total direct cost of US$86,413,971 and indirect cost of US$138,492,987. This resulted in an average incremental direct cost of US$2050 per RA patient. Within direct costs, the largest burdens were associated with drugs (US$73,028,944), laboratory tests (US$6,132,395), and hospitalizations (US$3,208,559). For indirect costs, absenteeism costs and presenteeism costs were US$16,059,681 and US$114,291,687, respectively. CONCLUSIONS: The economic burden of RA in Taiwan is driven by indirect healthcare costs, most notably presenteeism. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s40801-016-0063-8) contains supplementary material, which is available to authorized users.